Inhomogeneous energy transfer dynamics from iron-stress-induced protein A to photosystem I - Akhtar, Parveen; Jana, Sanjib; Lambrev, Petar H.; Tan, Howe-Siang (Frontiers in Plant Science, 2024)
Cyanobacteria respond to iron limitation by producing the pigment-protein complex IsiA, forming rings associated with photosystem I (PSI). Initially considered a chlorophyll-storage protein, IsiA is known to act as an auxiliary light-harvesting antenna of PSI, increasing its absorption cross-section and reducing the need for iron-rich PSI core complexes. Spectroscopic studies have demonstrated efficient energy transfer from IsiA to PSI. Here we investigate the room-temperature excitation dynamics in isolated PSI–IsiA, PSI, IsiA monomer complexes and IsiA aggregates using two-dimensional electronic spectroscopy. Cross analyses of the data from these three samples allow us to resolve components of energy transfer between IsiA and PSI with lifetimes of 2—3 ps and around 20 ps. Structure-based Förster theory calculations predict a single major timescale of IsiA-PSI equilibration, that depends on multiple energy transfer routes between different IsiA subunits in the ring. Despite the experimentally observed lifetime heterogeneity, which is attributed to structural heterogeneity of the supercomplexes, IsiA is found to be a unique, highly efficient, membrane antenna complex in cyanobacteria.